Analisis Wacana Kritis Buku Pengajian Ramadhan Kiai Duladi dan Implikasinya terhadap Pembelajaran: Model Fairclough - Aan Awaludin; Faznur, Lutfi Syauki (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Based on the ideal phenomenon of making any object a subject of discourse study, the author selects a book as the research object, using Norman Fairclough's theory as the analytical tool. Norman Fairclough's theory analyzes a text based on relations, identities, production, consumption, and socio-culture. The implementation of this theory is applied to the book titled Pengajian Ramadhan Kiai Duladi (Ramadhan Teachings by Kiai Duladi) to determine the author's intention within the text based on the text's production and the socio-cultural context of religious issues that occur during the month of Ramadhan. The research model used is qualitative descriptive. The research object is sourced from a title called Kiai Pemburu Dolar (Kiai the Dollar Hunter). For data collection, the author utilizes the documentation technique, gathering information or evidence through the examination of archives and documents that have been transcribed into written form. The results of the research conclude that, in the textual dimension, the book's author emphasizes the use of diction in their work. Meanwhile, in the discursive practice dimension, the author adjusts their status and educational background in the text's production, and the consumption is intended for all social levels. In the socio-cultural dimension, the author focuses more on social issues related to religion that frequently arise during the month of Ramadhan.